Modelling and Analysis of a Supply Chain with Supply, Production and Distribution Reliability Considerations - Ladi Ogunwolu; O. Ibidapo-Obe; Chidi Onyedikam (International Journal of Supply Chain Management, 2014)
This paper explores the effects of Supply, Production and Distribution reliabilities in a three-tier supply chain. The central thrust of the work is to examine and analyse on conceptual and analytical bases the effects of reliabilities of the systemic components of the Supply Chain on the overall cost of the Supply Chain. A linear cost-minimization Mathematical Programming Model of a three-stage supply chain is built in which the supply, production and distribution reliabilities determine supplier, production facility and distributor selections and contributing quantities to supplies, productions and distributions of goods respectively. Test experiments are designed as trade-offs of costs and reliabilities incorporated into the variants of the Mathematical Programming Model to study combinations of effects reliabilities on the cost structure of the Supply Chain.